Research of antioxidant and antimicrobial activity of aqueous alcoholic extracts from mycothallus and mycelium of Inonotus rheades (pers.) Bondartsev & Singer - T. G. Gornostay; V. A. Chkhenkeli; T. A. Penzina; M. S. Polyakova; G. B. Borovskiy (Acta Biomedica Scientifica, 2014)
We analyzed antioxidant and antimicrobial activity of aqueous alcoholic extracts from mycothallus and mycelium of Inonotus rheades. It was found that 70% aqueous alcoholic extracts from mycelium of I. rheades had the biggest antioxidant activity. 30% aqueous alcoholic extracts from mycothallus and mycelium have antimicrobial activity against the variety of microorganisms (Salmonella еnteritidis IMVL, Enterococcus faecalis ATSS 29217, Salmonella Ngor IMVL, Streptococcus spp. 44, Staphylococcus aureus ATSS 209p, Escherichia coli ATSS3 5218, Escherichia coli TI). We determined fungistatic activity of 30% aqueous alcoholic extracts of mycelium against Saccharomyces cerevisiae.